Unusual changes in the Antarctic Middle Atmosphere during the 2019 Warming in the Southern Hemisphere - S, Eswaraiah; Kim, Jeong-Han; Lee, Wonseok; Hwang, Junyoung; Kim, Yong Ha; Kondapalli, Niranjan Kumar (Zenodo, 2020)
For the Antarctic mesosphere study, we used wind measurements by the King Sejong Station (62.22 o S, 58.78°W) Meteor Radar (KSSMR).The KSS MR provides winds from the altitude 70 km to 100 km with 1 hour and 2 km height resolutions. Here we uploaded the dailyzonal and meridional winds during July to October of Southern Hemisphere. The data files contains the height and time evolution of wind components. Each file contains the height (First Column) and Winds (from Second column). The time period is from Julian Day 180 to 285 for the year 2019.